Design And Implementation of An Arduino Microcontroller Based Door Access Control System Using RFID Technology - Parthasarathy, Rajamohan; Ayyappan, Preethy; Loong, Seow Soon; Loong, Seow Soon; Sulaiman, Nor Anis Asma Binti; Rahman, Talha (International Journal of Psychosocial Rehabilitation, 2020)
All of the door opening system uses traditional ways such as lock and keys, latches, passcode or password locks. It encounters number of limitations that is, access is not time based and ID based facing lot of inconveniencies and drawbacks. In traditional systems there are no limitations on who can enter only manual control (security guards) are available. The focus is on implementation of an arduino based door unlocking system with real time control and implementing security system to avoid illegal and wrong time access. This hardware design and implementation would enable the user to use in real time practical condition. The RFID door lock is a unique lock that will allow the user to easily lock and unlock doors and it is also very simple to install. The door lock will have a RFID reader or writer and a door lock which is magnetic for simple use. When the door is locked, a LED will be turned on. The hardware components required are RFID reader, passive RFID tags, and an Arduino microcontroller. Additionally, there will be a light installed that will automatically switch on when the user unlocks the door and enters. Moreover, this door lock using RFID will be cost-effective and simple upgrade to the average consumer’s convenience and security.